Polyketide Synthase Gene Domain Exploration of Marine Sponge Symbiont Bacteria Collected From Weh Island - Sukmawan Fajar Santosa; Nazaruddin Nazaruddin; Wahyu Eka Sari; Febriani Febriani (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
Sponges have long been known as a source for isolating secondary metabolites. These natural compounds are biosynthetic products of symbiont bacteria from various phyla colonizing sponge tissue. Some symbiont bacteria are known to produce bioactive compounds that would have antibacterial activity, such as polyketide, due to competition in colonizing and obtaining nutrients from their hosts. In general, this study aims to explore the biosynthetic potential of seven sponge-symbiont bacteria by detecting the gene domain involved in the production of polyketide compounds. Sponge-symbiont bacteria isolation was carried out on one species of sponge collected from a depth of ±15 m in the Iboih area, Weh Island, Aceh Province, Indonesia. The bacteria was allowed to grow in Sea Water Complete agar medium and incubated at 280C for 10-14 days. The production of polyketide compounds involves the enzyme polyketide synthase (PKS). Polyketide synthase was detected by detecting the encoding gene domain involved in the production of polyketide compounds using PCR method. Five of the seven isolates of sponge symbiont bacteria were detected to contain the PKS gene domain. Furthermore, molecular identification confirm by 16S rRNA sequencing showed that the isolates belonged to the phylum Firmicutes and Actinobacteria. The result indicated that the sponge symbiont bacteria collected from Weh Island had the biosynthetic potential to produce polyketide compounds. These compounds would have antimicrobial activities that will play a major role in the medical field. Research related to screening PKS genes in marine sponge symbionts bacteria from Weh Island has never been reported before, thus adding to the novelty of this research.